UMPSA the only university in Malaysia to have an anechoic chamber for vehicle testing - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2024)
PEKAN, January 25, 2024 – Have we ever known that there is a room design that is recognised as the quietest place in the world?